Pengaruh Harga, Promosi Online, dan Rating Produk terhadap Minat Beli Konsumen Wardah di E-Commerce Shopee - Kristiana Pudji Astuti; Dian Ferriswara; Liling Listyawati; Galuh Ajeng Ayuningtyas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to examine the contribution of the Price Variable, Promotion Variable, and Product Rating Variable to Consumer Purchase Intention for Wardah cosmetic products on the Shopee e-commerce platform. The type of research used is a quantitative approach with data collection techniques through questionnaires distributed to respondents, namely consumers who have purchased Wardah cosmetic products on the Shopee e-commerce platform. The data obtained were analyzed using multiple linear regression techniques.The findings show that the Price variable contributes significantly, indicating that the more appropriate and affordable the price offered is in accordance with consumers’ perceived value, the higher their intention to purchase Wardah products on the Shopee e-commerce platform. Promotion is also proven to make a significant contribution to Purchase Intention, meaning that the more effective, informative, persuasive, and attractive the promotional activities are (both online and offline), the stronger the consumers’ motivation to purchase Wardah products on Shopee. Product Rating also has a significant contribution to Purchase Intention, indicating that the higher the ratings or positive reviews given by other users, the greater the consumers’ interest in purchasing Wardah products on Shopee. Good ratings can lower perceived risk, increase trust, and encourage consumers to make purchases, especially on e-commerce platforms.This research emphasizes the importance of pricing strategies, improving promotional quality, and managing product reviews and ratings as efforts to increase consumer interest and purchase decisions.